Self-Compassion dan Self-Esteem pada Narapidana - Nindy Amita; Juliarni Siregar; Nilla Listyani; Laras Assyfa (Jayapangus Press, 2023)
The purpose of the researchers was to find out whether self-compassion and self-esteem among inmates at Detention X. Researchers compared and identified the levels of self-compassion and self-esteem according to demographic data. The research sample was 145 male prisoners in prison. The sampling technique used purposive sampling method. The results of this study show that 18.7% of the sample is in low self-compassion and 30.35% of the sample is in the low self-esteem category. The results of the correlation analysis carried out in knowing the relationship of the two research variables is that there is a negative relationship between self-compassion and self-esteem. Self-compassion and self-esteem in prisoners with different forms of study so that the components seen correspond to the aspects in these variables. This study concluded that research respondents showed self-compassion and self-esteem had a negative relationship. In practical terms, the implications of this research can be used as an initial process to find out the description of the situation of prisoners in prisons.